Ceramic sculpture : making faces ; a guide to modeling the head & face with clay - Irvine, Alex. (Asheville : Lark Ceramics, 2014)
This is a step-by-step guide to sculpting the human face. It is richly illustrated with both photographs and diagrams for creating detail. It comes from experienced sculptor and instructor Alex Irvine. Sculpting the human face presents a unique artistic challenge, but this richly illustrated guide thoroughly demystifies the process. Instructor Alex Irvine goes step-by-step, explaining everything from creating basic, rough outlines to surface refinements to finely detailed replicas, accompanied by photographs and sketches.
Introduction -- Before You Begin -- Head Building Techniques -- Facial Features -- Facial Expressions & Aging -- Firing & Finishing Techniques -- Gallery -- Resources.
Includes bibliographical references (pages126-127) and index.
Keywords: Ceramic sculpture -- Technique; Face in art